Role of Angiopoietin/Tie2 in Critical Illness: Promising Biomarker, Disease Mediator, and Therapeutic Target? - Alexander Lukasz; Philipp Kümpers; Sascha David (Scientifica)
Critical illness is a descriptive, broad term for a serious clinical condition that can result from enormously heterogeneous etiologies. A common end feature these patients regularly suffer from is the so-called multiple organ dysfunction syndrome (MODS), often a consequence of organ hypoperfusion and ischemia, coagulopathies, overwhelming inflammatory responses, immune paralysis and mitochondrial dysfunction. Mechanistically, endothelial injury and particularly microvascular leakage is a major step in the pathophysiology of MODS and contributes to its mortality. The angiopoietin (Angpt)/Tie2 system consists of the endothelial tyrosine kinase Tie2 and its 4 circulating ligands (Angpt1-4). The balance between the agonistic ligand “Angpt-1" and the antagonistic one “Angpt-2" regulates baseline endothelial barrier function and its response to injury and is therefore considered a gatekeeper of endothelial activation. This paper provides a systematic overview of the Angpt/Tie2 system with respect to (1) its role as a global biomarker of endothelial activation in critical ill patients, (2) its contribution to MODS pathophysiology as a disease mediator, and last but not least (3) putative therapeutic applications to modify the activation state of Tie2 in mice and men.